أسرار التشابه اللفظي في تفسير الشيخ الشعراوي المتعلقة بالذكر والحذف (دراسة وصفية تحليلية): Secrets of verbal similarity in the interpretation of Sheikh Al-Shaarawi related to mention and deletion (a descriptive and analytical study) - Dr. Abdullah; Dr. Shakeel Ahmad (Al Manhal Research Journal, 2024)
The Praiseworthy Criterion is a miraculous book for creation in its style, eloquence, and organization, miraculous in its wisdom, knowledge, and the influence of its guidance. The topic of mention and deletion is one of the most important topics in the science of semantics, and it examines the coining of words, phrases, and sentences, in order to show the secrets and rhetorical advantages in them, and the Holy Qur’an is the best resource and it adds to that. Because of the abundance of words it contains and the multiplicity of meanings, it has occupied the world since its revelation, so scholars raced to research its words and methods and extract its secrets and pearls. Scholars have devoted themselves to studying everything related to the Book of God Almighty, including the issue of verbal similarity. After consideration and extrapolation, it became clear that Sheikh Al-Shaarawi’s interpretation is one of the interpretations that focused on this issue, hence the title of the topic “The Secrets of Verbal Similarity in Sheikh Al-Shaarawi’s Interpretation Related to The research includes an introduction, a preface, two sections, and a conclusion. The introduction shows the importance of the topic and the interest of Sheikh Al-Shaarawi in the chapter on verbal similarity, and the introduction sheds light on the author and the Book. The first section deals with the definition of mention and deletion, the definition of verbal similarity, its importance, its benefits, its secrets, and his most important works.